2016
DOI: 10.4028/www.scientific.net/kem.674.26
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Based Biocomposites: Mechanical Processing, Physical and Biological Properties

Abstract: Wood-based nanoparticles fabricated by different optimized methods – acid hydrolysis, thermocatalytic destruction and TEMPO catalysed oxidation – show the potential to improve the physical-mechanical and biological properties of polymer-matrix biocomposites. In this work, the influence of obtained nanoparticles on physical-mechanical and biological properties of chitosan-matrix biocomposite was investigated. The results showed that wood-based nanoparticles are promising constituents of polymer-matrix biocompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The synergistic effect between the two additives can be attributed to the intimate interaction between the cationic functional groups of chitosan and the NFC’s hydroxyl groups, as well as their high surface area, which facilitates strong bonds [ 25 , 26 , 27 , 28 ]. Studies on chitosan films with NFC additives have shown that the addition of NFC improved the mechanical and barrier properties of chitosan films, thus providing insight into the potential synergy of chitosan and NFC as additives in improving paper’s properties [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic effect between the two additives can be attributed to the intimate interaction between the cationic functional groups of chitosan and the NFC’s hydroxyl groups, as well as their high surface area, which facilitates strong bonds [ 25 , 26 , 27 , 28 ]. Studies on chitosan films with NFC additives have shown that the addition of NFC improved the mechanical and barrier properties of chitosan films, thus providing insight into the potential synergy of chitosan and NFC as additives in improving paper’s properties [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%